A geometry problem by Rakhi Bhattacharyya

Geometry Level 2

Find the value of:

( 1 cot 2 2 ) ( 1 cot 2 3 ) \large (1-\cot 22^\circ)(1-\cot 23^\circ)


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 13, 2016

( 1 cot 2 2 ) ( 1 cot 2 3 ) = ( 1 cos 2 2 sin 2 2 ) ( 1 cos 2 3 sin 2 3 ) = ( sin 2 2 cos 2 2 ) ( sin 2 3 cos 2 3 ) sin 2 2 sin 2 3 = sin 2 2 sin 2 3 + cos 2 2 cos 2 3 sin 2 2 cos 2 3 sin 2 3 cos 2 2 1 2 ( cos ( 2 3 2 2 ) cos ( 2 3 + 2 2 ) ) = cos 1 sin 4 5 1 2 ( cos 1 cos 4 5 ) = cos 1 1 2 1 2 ( cos 1 1 2 ) = 2 \begin{aligned} (1-\cot 22^\circ)(1-\cot 23^\circ) & = \left(1 - \frac {\cos 22^\circ}{\sin 22^\circ}\right) \left(1 - \frac {\cos 23^\circ}{\sin 23^\circ} \right) \\ & = \frac {(\sin 22^\circ -\cos 22^\circ)(\sin 23^\circ -\cos 23^\circ)}{\sin 22^\circ \sin 23^\circ} \\ & = \frac {\sin 22^\circ \sin 23^\circ + \cos 22^\circ \cos 23^\circ - \sin 22^\circ\cos 23^\circ -\sin 23^\circ\cos 22^\circ }{\frac 12 \left(\cos (23^\circ - 22^\circ) - \cos (23^\circ + 22^\circ) \right)} \\ & = \frac {\cos 1^\circ - \sin 45^\circ}{\frac 12 \left(\cos 1^\circ - \cos 45^\circ \right)} \\ & = \frac {\cos 1^\circ - \frac 1{\sqrt 2}}{\frac 12 \left(\cos 1^\circ - \frac 1{\sqrt 2} \right)} \\ & = \boxed{2} \end{aligned}

Viki Zeta
Oct 12, 2016

cot ( 45 ) = 1 cot ( 22 + 23 ) = 1 ( cot 22 cot 23 1 ) cot 22 + cot 23 = 1 cot 22 cot 23 1 = cot 22 + cot 23 cot 22 cot 23 cot 22 cot 23 = 1 cot 22 ( cot 23 1 ) cot 23 = 1 cot 22 ( cot 23 1 ) cot 23 + 1 = 2 cot 22 ( cot 23 1 ) ( cot 23 1 ) = 2 ( 1 cot 22 ° ) ( 1 cot 23 ° ) = 2 \cot(45) = 1 \\ \cot(22 + 23) = 1 \\ \dfrac{(\cot 22 \cdot \cot 23 - 1)}{\cot 22 + \cot 23} = 1 \\ \cot 22 \cot 23 - 1= \cot 22 + \cot 23 \\ \cot 22 \cot 23 - \cot 22 - \cot 23 = 1 \\ \cot 22 \left(\cot 23 - 1\right) - \cot 23 = 1 \\ \cot 22 \left(\cot 23 - 1\right) - \cot 23 + 1 = 2 \\ \cot 22 \left(\cot 23 - 1\right) - \left(\cot 23 - 1\right) = 2 \\ (1-\cot 22°)(1-\cot 23°) = 2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...